Unveiling final-year students and new graduates’ concerns, preparedness, and learning experiences during the pandemic in Qatar: A cross-sectional survey - Yasin M. Yasin (14779381) (2023)
Background The emergence of COVID-19 interrupted education worldwide and educational institutions were forced to switch to an online learning (E-learning) environment. Objectives To explore the perceived educational experiences, worries, and preparedness to enter clinical practice among final-year nursing students and new graduate nurses after studying during the COVID-19 pandemic. Design A cross-sectional survey design. Setting and participants: An online survey of final-year undergraduate Bachelor of Nursing Students at a single university in Qatar and new graduates across 14 health facilities in Qatar was undertaken between May 2022 and July 2022. Methods Participant demographics, experiences of E-learning and perceptions of readiness for practice were collected using validated instruments and open-ended questions. Descriptive statistics and thematic exploration were used to analyze the data. Results Fifty-nine final-year students and 23 new graduates with an average age of 23.95 years (SD = 3.89) responded to the survey. Face-to-face clinical placement learning was preferred by 50 % of students and 66.1 % of graduates. During COVID-19, the majority of the participants indicated that strategies like practice kits and online simulations were implemented. While 61 % of new graduates felt well-prepared in their nursing skills, and 87 % felt confident, less than half of the students still in their final year of education felt prepared or confident. Increased stress and a perceived impact on education quality were reported due to changes in learning modalities. Despite these challenges, 81.1 % of students and 95.7 % of graduates felt they had developed sufficient professional values, with most looking forward to becoming registered nurses. The qualitative themes that emerged related to 1) adjusting to online learning, 2) experiencing restrictions in clinical learning skills, 3) feeling less confident and 4) experiencing increased stress. Conclusions Despite experiencing emotional and educational challenges, the participants in this study felt that their education prepared them for clinical practice. Innovative strategies and unique educational experiences used by educators enhanced participants' clinical skills and readiness for practice. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2023.e22337